2021
DOI: 10.1177/02666669211010872
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of egovernment adoption amidst COVID-19 pandemic: The Information Adoption Model (IAM) approach

Abstract: The study scrutinized the behavioral adoption of informational e-government services among Chinese citizens in the midst of the COVID-19 pandemic. A structural equation modeling (SEM) technique was applied for the data analysis using Smart PLS 3.0 statistical software. The results show that information quality, information credibility, and ease of COVID-19 informational e-government services are significant in determining citizens’ perception of the usefulness of COVID-19 information shared on e-government pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 64 publications
3
15
0
Order By: Relevance
“…Evan and Erkan (2016) and Sussman and Siegal (2003) found information quality as the main predictor of information usefulness. Users believe that high-quality information produces useful information (Jiang et al, 2021;Mensah et al, 2021). Leong et al (2022) mentioned that the quality of the information can be assessed through accuracy, completeness, and timeliness.…”
Section: Information Quality (Iq) and Information Usefulness (Iu)mentioning
confidence: 99%
“…Evan and Erkan (2016) and Sussman and Siegal (2003) found information quality as the main predictor of information usefulness. Users believe that high-quality information produces useful information (Jiang et al, 2021;Mensah et al, 2021). Leong et al (2022) mentioned that the quality of the information can be assessed through accuracy, completeness, and timeliness.…”
Section: Information Quality (Iq) and Information Usefulness (Iu)mentioning
confidence: 99%
“…Research suggests that the use of social media (e.g., Tiktok) can encourage the uptake of public health information and promote physical and mental health (Basch et al, 2020). Elsewhere, Mensah et al (2021) found that information quality has a positive effect on the perceived usefulness of COVID-19 informational e-government services. Many governments actively disseminate information relevant to the pandemic through various social media platforms (e.g., micro-blogs, WeChat, Tiktok, and Twitter), as well as refuting false rumors and misinformation.…”
Section: Pandemic Prevention Knowledge As the Mediator In The Informa...mentioning
confidence: 99%
“…A study in China found that ease of access to information services and the reliability of COVID-19 data are critical to citizens. When satisfied with these parameters, citizens consider the services useful and are ready to recommend them to their friends [16].…”
Section: Literature Reviewmentioning
confidence: 99%